2001
DOI: 10.1557/s109257830000017x
|View full text |Cite
|
Sign up to set email alerts
|

New Technique for Sublimation Growth of AlN Single Crystals

Abstract: Single crystalline platelets of aluminum nitride (AlN) were successfully grown by a new technique. It consists of (1) depositing an AlN buffer layer on a SiC substrate by metal organic chemical vapor deposition (MOCVD) below 1100°C, (2) forming an (AlN)x(SiC)1−x alloy film on the AlN film by condensing vapors sublimated at a temperature of 1800°C from a source mixture of AlN-SiC powders, followed by (3) condensing vapors sublimated from a pure AlN source (at 1800°C). The necessity of the first two steps for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“… = 23°, we were able to incorporate as much as 18 % at of silicon in the bulk volume. The even higher Si content in samples of Gu et al [13,18] and Shi et al [17] makes clear, however, that the silicon content in our samples does not reach the 'kinetic limit' of Si incorporation, above which the Si content does not depend on supply anymore.…”
Section: Chemical Analysiscontrasting
confidence: 61%
See 1 more Smart Citation
“… = 23°, we were able to incorporate as much as 18 % at of silicon in the bulk volume. The even higher Si content in samples of Gu et al [13,18] and Shi et al [17] makes clear, however, that the silicon content in our samples does not reach the 'kinetic limit' of Si incorporation, above which the Si content does not depend on supply anymore.…”
Section: Chemical Analysiscontrasting
confidence: 61%
“…Shi et al [17] used a sintered AlN-SiC compound source and Si-face 6H-SiC seeds with AlN epitaxial layers on top to grow AlN-SiC films in tungsten crucibles at 1800°C. They found an Al:Si ratio of 4:1 in the crystals independent of the source composition.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of substrate misorientation and buffer layers on growth modes and defects in AlN sublimed onto 6H-SiC substrates were studied in Refs. (Shi et al, 2001), (Yakimova et al, 2005); different growth modes were related to the low mobility of AlN adatoms on the crystal surface. The grown bulk AlN crystals (the typical growth rate is about 100 µ/hour) usually have the rough side surface while the top surface could be facetted.…”
Section: Sublimation Growth Of Aln Crystalsmentioning
confidence: 99%
“…Numerous studies of heteroepitaxially grown nitride films indicate that defect structures include threading dislocations, stacking faults, nanopipes, and inversion domains (IDs). Due to its close lattice match with AlGaN, similar coefficient of thermal expansion, wide bandgap, high thermal conductivity, and high chemical and thermal stability, single crystal AlN is an excellent candidate as a III-nitride substrate material [2]. Bulk AlN crystals grown by the sublimation-recondensation technique have been reported [3,4], but presently, large AlN single crystals are still not available in large quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk AlN crystals grown by the sublimation-recondensation technique have been reported [3,4], but presently, large AlN single crystals are still not available in large quantities. Seeded growth of AlN on SiC has been studied by a number of groups [2,[5][6][7] as a way to exploit the availability of large, high-quality SiC substrates and to control the polarity and orientation of AlN crystals. These studies identified a number of issues associated with this technique, including the stability of the SiC seeds, the growth mode of AlN, the presence of defects in the grown layers, and postgrowth cracking of the AlN layers due to the thermal expansion coefficient mismatch.…”
Section: Introductionmentioning
confidence: 99%